From manners to rules : advocating for legalism in South Korea and Japan / Celeste L. Arrington. - Arrington, Celeste L., 1980- (Cambridge studies in law and society., 2025)
From Manners to Rules traces the emergence of legalistic governance in South Korea and Japan. While these countries were previously known for governance characterized by bureaucratic discretion and vague laws, activists and lawyers are pushing for a more legalistic regulatory style. Legalism involves more formal, detailed, and enforceable rules and participatory policy processes. Previous studies have focused on top-down or structural explanations for legalism. From Manners to Rules instead documents bottom-up sources of institutional and social change, as activists and lawyers advocate for and use more formal rules and procedures. By comparing recent reforms in disability rights and tobacco control, the book uncovers the societal drivers behind legalism and the broader judicialization of politics in East Asia's main democracies. Drawing on 120 interviews and diverse sources, From Manners to Rules challenges the conventional wisdom that law and courts play marginal roles in Korean and Japanese politics and illuminates how legalistic governance is transforming citizens' options for political participation.